A Modified Technique of Thulium Laser Enucleation for Benign Prostatic Hyperplasia With Non-morcellator Approach - Jing, Yifeng; Sun, Qian; Guo, Wenhuan; Zhou, Dapeng; Zhu, Yiping; Zhao, Yuyang; Cui, Di; Wang, Xiaohai; Ruan, Yuan; Zhao, Fujun; Xia, Shujie; Han, Bangmin (Frontiers in Surgery, 2021)
Background: Until recently, most enucleation techniques of the prostate were performed with the application of morcellator. We introduce a modified enucleation technique of thulium laser with non-morcellator approach, which is about incising and vaporizing remaining prostate tissue instead of a morcellator. Methods: A retrospective evaluation of 223 patients undergoing ThuLEP from January 2014 to December 2015 was performed in our institution. One hundred five of the patients used morcellator while the other 118 used non-morcellator approach. All patients were assessed with the International Prostate Symptom Score (IPSS), quality of life (Qol), ultrasonography, serum prostate-specific antigen (PSA), maximal urine flow rate (Qmax), and postvoid residual urine volume (PVR). We reassessed these parameters at 1-, 3-, 6-, and 12-months after operation. Operative time, perioperative, and postoperative complications were also recorded. Results: Significant improvement was noted in the IPSS, QoL, Qmax, and PVR in both groups at the 12-month follow-up, and assessment showed no differences in these parameters between the two groups. Comparisons of the total operation time and enucleation time demonstrated no significant differences between the two groups. Our non-morcellator approach needed more time to incise and vaporize the enucleated tissue compared to morcellation when the prostate volume was about 40–80 ml (p < 0.05), while it showed a significant lower rate of superficial bladder injury than using morcellator (p < 0.05). There were no significant differences in other complications between the two groups (p > 0.05). Conclusions: Our modified technique is a safe and effective procedure for the treatment of BPH avoiding the potential complications caused by morcellator.